Using linear programming to determine the optimal composition of production in light of scarcity of economic resources available to economic (Entrepreneurship Journal for Finance and Business, 2023)
The establishment is considered the center of strength for the economy of any country by meeting the needs of the community in terms of goods and services. Determining the optimal combination of production in light of the constraints of energy and demand is one of the most important pillars of the success of the establishment or factory in the market, noting that it depends on searching for the desired quantities of products based on the limited and scarcity of resources and energies. productivity required for production.The linear programming model is among the most important quantitative methods used in building the mathematical model that enables decision-makers and those in charge of implementing them to reach the required goals in light of the available capabilities, as it is used to determine the optimal distribution of scarce resources, which usually include raw materials involved in the production process and machinery. equipment, allotted time and capital, and it is applied to many work problems and in various fields such as finance, production, marketing, distribution, etc.